Ovo-novelo-novo-no-velho: análise comparativa das antologias de poesia concreta - Marina Ribeiro Mattar (2024)
This thesis is the first detailed study of Brazilian and international anthologies of Concrete Poetry. It aims to fill a historical gap in the research developed in the country, through a transnational investigation focused on the production of anthological printed matter published in different media: magazines, catalogs and books. The comparative study aimed to examine anthologies of concrete poetry at national and international level, reflecting on the main criteria for the composition of the selections, such as the participating agents, the ordering of the material, the profile of the organizers and the appearance of supporting texts and their contents. To this end, anthologies of Brazilian concrete poetry published inside and outside the country were analyzed in order to understand the parameters established by the anthologists to present, discuss and publish selections of poems by the São Paulo group. The thesis also sought to discuss the foreign reception of the Noigandres group, especially in its years of greatest activity, between 1955 and 1970. The printed matters chosen to compose the corpus of the work were anthologies of concrete poetry with an international slant published between 1959 and 1969, especially the books produced as a result of the Brazil-Germany relationship, in dialogue with the Stuttgarter Gruppe, whose selection included one or more Brazilian concrete poets. The comparative analysis provided a historical overview of the Brazilian concretism mediated by the anthologies, bringing a complementary view to revisionist studies and opening up new possibilities of reception for the concrete legacy in an expansion of sources and period documents.